Development of a Portable Universal Testing Machine for Investigating the Mechanical Properties of Medium-Strength Materials - Aulia, Udink; Yudiansyah, Radinal; Rizal, Muhammad (Aceh International Journal of Science and Technology, 2023)
The tensile test is reliable for revealing the fundamental stress-strain relationship. However, researchers have challenges when applying sufficient equipment to comprehend and assess the tensile characteristics of low-to-mediumstrength materials. This study describes the design and construction of a portable universal testing machine (UTM) for investigating the mechanical characteristics of medium-strength materials. The components of this machine include two stepper motors, a load cell, a load cell amplifier, a linear potentiometer, and a data acquisition system. The capability of this machine component is designed for a load of 10 kN with a maximum stroke of 150 mm with vertical motion. Samples of jute and glass fiber composites were tested at room temperature on this machine. The generated results were compared with those obtained from a commercial UTM to validate the developed machine. The values of the mechanical characteristics that a commercial UTM measured are quite similar to those acquired from the measurements that were taken by this machine. The conclusion is that this testing machine is simple, portable, reliable, and might be constructed cheaply